Diasporic Female Identities in Bharati Mukherjee's Desirable Daughters and Idris Ali's Dongola. - Koraa, Rola Alaa (AUC Knowledge Fountain, 2016)
This thesis attempts to explore the development of female identities in two contemporary diasporic novels Bharati Mukherjee’s Desirable Daughters (2002) and Idris Ali’s Dongola (1993) that tackle the notion of diaspora differently. Desirable Daughters portrays the modern type of diaspora, that of immigration, while Dongola portrays the Nubian diaspora as a typical classical diaspora. The main goal of the thesis is to examine the different implications of diaspora on the protagonists’ identity formation as females in order to know where they fit in the diasporic spectrum. Tara and Halima share some major factors such as being members of ethnic minorities, and being brought up in oppressive patriarchal societies. Each has a different notable experience in terms of individual and social identity transformation due to physical or metaphorical displacement. The thesis will read their different diasporic experiences through intersectionality feminism which is a paradigm of interlocking systems of oppression based on race, class, and gender. The identities of both characters are analyzed against the three factors which are integral to the idea of diaspora. Each of these factors may be looked upon differently after the character’s displacement resulting in the character’s identity development. The three axes of the intersectionality theory pave the way for understanding the similarities and differences between Tara and Halima in relation to their diasporic situation. Tara discovers her true self and accepts her dual identity after returning to India, while Halima’s total loss of her homeland, Nubia, and her husband results in her violent revenge at the end.